Concomitant Correction of a Soft-Tissue Fenestration with Keratinised Tissue Augmentation By Using A Rotated Double-Pedicle Flap During Second-Stage Implant Surgery- A Case Report - Aileni Amarender Reddy; P. Anoop Kumar; Sistla Sailaja; YSHS Chakravarthy; Rampalli Viswa Chandra (Journal of Clinical and Diagnostic Research, 2015)
Soft tissue deficiencies and defects around dental implants have been observed frequently. Soft-tissue defects after implant procedures originate from the process of modelling of periimplant mucosa and often cause aesthetic disharmony, food debris accumulation and soft tissue shrinkage. Periimplant mucogingival surgery focuses on creating an optimum band of keratinized tissue resulting in soft tissue architecture similar to the gingiva around natural teeth. A 23-year-old male reported to the Department of Periodontology with a complaint of gum soreness, foul smell and food accumulation at a site where a 3.75 x 11.5mm implant was placed previously. On clinical examination, fenestration of tissue above the cover screw was observed and there appeared to be a keratinized tissue of 1mm surrounding the implant. The case was managed by use of a rotated double-pedicle flap during second-stage implant surgery to correct the soft-tissue fenestration defect and to obtain a keratinized periimplant soft tissue. A periosteal bed was prepared by giving a horizontal incision at the mucogingival junction to a depth of 4 mm. Two split-thickness keratinized pedicles were dissected from the mesial and distal interproximal tissues near the implant. After rotation, both the pedicles were sutured to each other mid-buccally and the pedicles were rigidly immobilized with sutures. At 1 month, there was a 3mm band of stable and firm keratinized tissue over the underlying tissues. The procedure resulted in an aesthetic improvement due to enhanced soft tissue architecture and optimum integration between the periimplant soft tissue and the final prosthesis.